2009
DOI: 10.1016/j.marenvres.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphological mechanisms leading to hypoxia off the Changjiang estuary

Abstract: Based on the seasonal surveying data and long-term data, the annual changes in the geographical locations, occurrence frequency, affected areas and the minimum oxygen level as well as the formation mechanism of the summer hypoxia off the Changjiang estuary are summarized and discussed in this paper. The historical data indicates that there were episodes of hypoxia in the past 50 years but not every year, and the event of summer hypoxia could be traced back to as early as late 1950s off the Changjiang estuary. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 19 publications
5
64
1
3
Order By: Relevance
“…The discharge of Changjiang is highly seasonal with its peak in summer and 75% of the river runoff occurring during the flood/rainy season between May and October (Rabouille et al, 2008). The hypoxia adjacent to the Changjiang Estuary, which is one of the largest coastal low-oxygen areas in the world , always occurs in summer and its zone has increased in recent decades (Rabouille et al, 2008;Wang, 2009). Wang et al (2012) also noted that the increasing trend of hypoxia would continue in next two decades.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The discharge of Changjiang is highly seasonal with its peak in summer and 75% of the river runoff occurring during the flood/rainy season between May and October (Rabouille et al, 2008). The hypoxia adjacent to the Changjiang Estuary, which is one of the largest coastal low-oxygen areas in the world , always occurs in summer and its zone has increased in recent decades (Rabouille et al, 2008;Wang, 2009). Wang et al (2012) also noted that the increasing trend of hypoxia would continue in next two decades.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…Besides the consumption of oxygen from the organic matter decomposition, physical forcings (stratification, circulation pattern in the region and residence time of the water in the mixing zone) which limit oxygenation of bottom waters were also important factors in the formation of hypoxic off the Changjiang Estuary (Wei et al, 2007;Rabouille et al, 2008;Wang, 2009). In late spring, the combination of high CDW runoff, TWC and strong solar radiation made a strong stratification in the northern ECSS (Wang, 2009). The decomposition of organic matter consumed oxygen, while oxygen could not be replenished due to the strong stratification in late spring.…”
Section: Relationships Between Summer Hypoxia and Seasonal Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypoxic condition off the Changjiang Estuary (CE) has been detected since the 1950s. The lowest DO concentrations in this region have continually decreased, and the summertime hypoxic zone has continually spread since 2003 [Chen et al, 2007;Wei et al, 2007;Wang, 2009;Ning et al, 2011]. Early hydrological surveys off the CE found that hypoxia occurred in a region approximately 100 km east of the river mouth along 123 E and at a depth of 35 m [Tian et al, 1993].…”
Section: Introductionmentioning
confidence: 99%